Penyelesaian Sengketa Wanprestasi Kredit Macet di BUMDesMa Kanor Mandiri Berkah Kabupaten Bojonegoro - Emir Muhammad Adiel Mahendra; Kurniasih Bahagiati (Sharia Faculty of Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, 2026)
One of the initiatives by BUMDesMa Kanor Mandiri Berkah in Kanor District, Bojonegoro Regency, is the Dana Bergulir Masyarakat (DBM) savings and loan program, which encounters challenges related to loan defaults and breach of contract by borrowers. BUMDesMa adopts a non-litigation approach, specifically mediation, to resolve disputes. This study seeks to elucidate the dispute resolution process in cases of loan defaults at BUMDesMa Kanor Mandiri Berkah and to examine the challenges encountered during this process. Employing an empirical juridical research method with a sociological approach, the study gathered data through interviews with key personnel at BUMDesMa. Data analysis involved verification, classification, and conclusion. The results reveal that the mediation process at BUMDesMa Kanor Mandiri Berkah has limitations in effectively resolving disputes, with several obstacles impeding the resolution process.